التغير المناخي وتحديات تحقيق مدن صحية في مصر Climate Change challenges to achieve Healthy Cities in Egypt - Heba Mahrous Ali Abd El Aal (Journal of Urban Research, 2023)
التغير المناخي أصبح مشكلة عالمية ويترتب عليه الكثير من المشكلات التي تؤثر بشكل مباشر على حياة الأفراد. وهذا الأمر البيئي له مسببات مباشرة وغير مباشرة يتسبب بها الفرد، وبالتالي يتأثر بها في صور مختلفة قد تؤدى إلى مستوي معيشي سيء نتيجة لتدهور البيئة الطبيعية، موارد الطاقة، الانبعاثات الكربونية إلى جانب التأثير السلبي على صحة الأفراد. وأهداف الاستدامة تطالب بتحقيق مدن آمنة، مستدامة ومرنة مثل المدن الصحية للتكيف مع التغير المناخي وما يترتب عليه. لهذا كان توجه الورقة البحثية نحو تقديم حل إلزامي لتحسين بيئة الأفراد في مواجهة تلك المؤثرات من أجل تحقيق مدن صحية توفر جودة الحياة وخاصة على النطاق المحلى. فتناولت الورقة البحثية توضيح مفهوم التغير المناخي من مسببات وعوائق وعلاقته بالمدن وقاطنيها وصولا إلى أهمية تحقيق مدن تتناول جودة معيشية للأفراد قاطنيها حتى يتحقق مفهوم المدن الصحية. لذلك فقد اعتمد البحث على المنهج الاستقرائي حيث يقوم البحث بتناول المفاهيم والمعايير التي توضح ماهية المدن الصحية ومقارنتها بالمدن التقليدية يليه تحليل لمعايير المدن الصحية وعمل استبانة لمتخصصين وغير متخصصين لإدراك مدى الوعي البيئي وتقييمهم لآليا ت ومعايير تصميم المدينة الصحية من أجل الوصول لمخطط تنفيذي لتحويل المدن التقليدية لمدن صحية داخل مصر. Climate change has become a global problem with many problems directly affecting people's lives. This environmental order has direct and indirect causes caused by the individual and is therefore influenced in diverse ways that may lead to a poor standard of living because of the degradation of the natural environment, energy resources, carbon emissions and the negative impact on individuals' health. Sustainability goals demand safe, sustainable, and resilient cities such as healthy cities to adapt to climate change and its consequences. The paper was therefore geared towards providing a compulsory solution to improve people's environment in the face of those impacts to achieve healthy cities that provide quality of life, especially on the local scale. The paper explains the concept of climate change as a cause and impediment and its relationship with cities and their inhabitants to achieve cities that address the quality of life of their inhabitants so that the concept of healthy cities can be achieved. The research is based on the inductive approach. The research addresses the concepts and criteria that illustrate what healthy cities are and compare them with traditional cities. That followed by an analysis of the standards of healthy cities and a questionnaire of specialists and non-specialists to understand the extent of environmental awareness and their assessment of the mechanism and the design criteria of a healthy city to achieve an operational scheme to transform traditional cities into healthy cities within Egypt.